Effect of Peptides on the Inactivation of Tissue Plasminogen Activator by Plasminogen Activator Inhibitor-1 and on the Binding of Tissue Plasminogen Activator to Endothelial Cells - Wittwer, A J; Sanzo, M A (Thrombosis and Haemostasis, 1990)
The effectiveness of tissue plasminogen activator (tPA) in thrombolytic therapy is dependent upon the rate at which therapeutically administered tPA reaches the clot site and the proportion of that tPA which is enzymatically active. Interactions between tPA and its main plasma inhibitor (PAI-1) and between tPA and the endothelial cells lining blood vessels are two factors which may limit efficacy. In an attempt to identify the regions of the tPA molecule involved in these interactions, we have examined a series of synthetic peptides with amino acid sequences corresponding to different regions of the tPA molecule for their ability to protect tPA from inactivation by PAI-1 and for their ability to reduce the binding of tPA to endothelial cells. Three peptides were identified which were especially effective at maintaining tPA activity in the presence of PAI-1 and three others were found which had a lesser effect. These same peptides were also found to inhibit the binding of tPA to endothelial cells. This suggests that the same regions of the tPA molecule are involved in both processes. None of the peptides inhibited the binding of tPA to fibrin. These peptides may serve as models for the development of agents for enhancing the activity of both endogenous tPA and of tPA administered in thrombolytic therapy.